Molecular Mechanism and Potential Targets for Blocking HPV-Induced Lesion Development - Guzmán-Olea, E. (Hindawi Publishing Corporation, 2012)
Persistent infection with high-risk HPV is the etiologic agent associated with the development of cervical cancer (CC) development. However, environmental, social, epidemiological, genetic, and host factors may have a joint influence on the risk of disease progression. Cervical lesions caused by HPV infection can be removed naturally by the host immune response and only a small percentage may progress to cancer; thus, the immune response is essential for the control of precursor lesions and CC. We present a review of recent research on the molecular mechanisms that allow HPV-infected cells to evade immune surveillance and potential targets of molecular therapy to inhibit tumor immune escape.